Spectrum of genetic variation in selection schemes of Desi chickpea (Cicer arietinum L.) - M. R . Paneliya Mehta D. R.; Raval Lata J. and; Chetariya C. P (Electronic Journal of Plant Breeding, 2017)
An experiment was conducted to study the spectrum of genetic variation for seed yield per plant and its component traits in the four selection procedures [PS(EF), PS(HY), SSD and RBP] each with 20 progenies in GJG 0315 x ICCV 96029 in F5 generation in Desi chickpea (Cicer arietinum L.). Analysis of variance revealed significant genotypic differences for all the characters with wide range of variation. Out of the total 6 cases studied in F5, PS(EF) in 2 cases; SSD in 3 cases sand PS(HY) in 1 case were better for depicting the widest phenotypic range and maximum coefficient of range, irrespective of characters. Moderate to high heritability and genotypic co-efficient of variation coupled with high expected genetic advance as per cent of mean was observed for number of branches per plant by PS(HY) and RBP and for 100-seed weight in PS(EF), PS(HY) and SSD of this cross which indicated the predominant role of additive gene action in the expression of these traits in respective breeding schemes.